2014
DOI: 10.1167/iovs.13-12811
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Retinal Nerve Fiber Layer Thickness and Axonal Transport 1 and 2 Weeks After 8 Hours of Acute Intraocular Pressure Elevation in Rats

Abstract: Acute IOP elevation to 50 mm Hg for 8 hours does not cause a persisting axonal transport deficit at 1 or 2 weeks or a detectable RNFLT or RGC loss by 6 weeks but does lead to transient RNFL thickening that resolves by 3 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 94 publications
6
53
1
Order By: Relevance
“…Since both estimates contain inherent error, Deming regression was applied to determine the slope and intercept of the relationship, which resulted in the following equation: RGC density by CSLO in vivo (per mm 2 ) = 0.58*RGC density by microscopy ex vivo (per mm 2 )+103 (per mm 2 ), similar to the findings in two of our previous studies [26], [39]. There is evidence in these data of “saturation” whereby a quadratic model provided a statistically better fit than a linear model (F = 13, p = 0.001), suggesting that the resolution of the in vivo CSLO method places an upper limit on density measurements.…”
Section: Resultssupporting
confidence: 54%
“…Since both estimates contain inherent error, Deming regression was applied to determine the slope and intercept of the relationship, which resulted in the following equation: RGC density by CSLO in vivo (per mm 2 ) = 0.58*RGC density by microscopy ex vivo (per mm 2 )+103 (per mm 2 ), similar to the findings in two of our previous studies [26], [39]. There is evidence in these data of “saturation” whereby a quadratic model provided a statistically better fit than a linear model (F = 13, p = 0.001), suggesting that the resolution of the in vivo CSLO method places an upper limit on density measurements.…”
Section: Resultssupporting
confidence: 54%
“…Beyond its use as a neuronal tracer (see transport section above), retrogradely transported CTB effectively labels RGC cell bodies in the retina (Abbott et al, 2013(Abbott et al, , 2014. Recent studies from our group have shown CTB labeling in the cytoplasm and axons of RGCs after SC application, showing good correspondence with the RGC marker Brn3a (Fig.…”
Section: Cholera Toxin B (Ctb)mentioning
confidence: 72%
“…Presently, although surgery or drugs are often used to control IOP, patients with controlled IOP still suffer from optic atrophy and RGC apoptosis [25, 26]. Additionally, as an inhibitor of proteasomes and calpain, N-acetyl-leucyl-leucyl-norleucinal (ALLN) treatment may promote cell death of primary retinal neurons via the necrosis and apoptosis [27].…”
Section: Discussionmentioning
confidence: 99%